2006
DOI: 10.1103/physreve.74.016112
|View full text |Cite
|
Sign up to set email alerts
|

Topology regulates the distribution pattern of excitations in excitable dynamics on graphs

Abstract: We study the average excitation density in a simple model of excitable dynamics on graphs and find that this density strongly depends on certain topological features of the graph, namely connectivity and degree correlations, but to a lesser extent on the degree distribution. Remarkably, the average excitation density is changed via the distribution pattern of excitations: An increase in connectivity induces a transition from globally to locally organized excitations and, as a result, leads to an increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…In this range of f the distribution patterns of excitations are dominated by burst regimes (as discussed in [36]. The pattern formation for f >0.1 is strongly influenced by random firing events, while for f <10 −3 the modular boundaries are followed only partly by the dynamics, hinting at another form of correlation between dynamics and topology, which acts on a larger topological scale.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In this range of f the distribution patterns of excitations are dominated by burst regimes (as discussed in [36]. The pattern formation for f >0.1 is strongly influenced by random firing events, while for f <10 −3 the modular boundaries are followed only partly by the dynamics, hinting at another form of correlation between dynamics and topology, which acts on a larger topological scale.…”
Section: Resultsmentioning
confidence: 89%
“…Other variants of three-state excitable dynamics have been used to describe epidemic spreading [31]–[34]. As discussed previously [35],[36], this general model can readily be implemented on arbitrary network architectures. It has been shown that short-cuts inserted into a regular (e.g., ring-like) architecture can mimic the dynamic effect of spontaneous excitations [35].…”
Section: Introductionmentioning
confidence: 99%
“…The three-state UAR description introduced above is reminiscent of Susceptible–Excited–Refractory (SER) models widely adopted to study network signal propagation (Dodds and Watts, 2004; Müller-Linow et al, 2006; Centola et al, 2007; Müller-Linow et al, 2008; Hütt et al, 2012) except that our definition of p U→A i takes into account the two-hop neighborhood of each astrocytes, i.e., the activation state of neighbors of the cells coupled to each astrocyte. If the status of activation of the two-hop neighborhood is indeed crucial in ICW propagation, then we expect that the essence of ICW dynamics in the astrocyte networks considered so far, will be reproduced if we substitute the ChI astrocyte model by the UAR description.…”
Section: Resultsmentioning
confidence: 99%
“…The mean field approximation (MFA) has been applied to investigate the dynamics and steady state of propagation models, such as the forest fire [31,32,33] and epidemiological models [33,34,35] in complex networks. In this framework, the steady-state equilibrium forest density of the cellular-automata model defined by the above rules (1)- (5) is studied following the approach defined in reference [36] for a similar CA model.…”
Section: Mean-field Approachmentioning
confidence: 99%